The role of eggs in the diet: nutraceutical and epigenetic aspects - G. Caramia; D. Degl'Innocenti; M. Mozzon; D. Pacetti; N.G. Frega (PAGEPress Publications, 2012)
The use of eggs in human diet has been object of many prejudices which are not yet completely disappeared The evolution of knowledge in the field of nutrition has, partially, countered these prejudices by highlighting the biological importance of several compounds present in the eggs. The nutritional and commercial revaluation of the eggs are passed through the enrichment of the lipid fraction in ω3 polyunsaturated fatty acids (PUFA ω3) which, have shown positive effects against cardiovascular diseases and development of the central nervous system and retina. The enrichment of eggs lipid with ω3 fatty acids is carried out by the integration of feeding hens with oils rich in ω3 fatty acids such as plant or marine oils. The results showed that the accumulation of ω3 in the egg yolk lipids is strongly affected by the type of oil used as supplement and by the amounts of oils administrated to the hens.